2012
DOI: 10.1002/chir.22080
|View full text |Cite
|
Sign up to set email alerts
|

Stereoselective Binding of Flurbiprofen Enantiomers and their Methyl Esters to Human Serum Albumin Studied by Time‐Resolved Phosphorescence

Abstract: The interaction of the nonsteroidal anti-inflammatory drug flurbiprofen (FBP) with human serum albumin (HSA) hardly influences the fluorescence of the protein's single tryptophan (Trp). Therefore, in addition to fluorescence, heavy atom-induced room-temperature phosphorescence is used to study the stereoselective binding of FBP enantiomers and their methyl esters to HSA. Maximal HSA phosphorescence intensities were obtained at a KI concentration of 0.2 M. The quenching of the Trp phosphorescence by FBP is main… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 33 publications
0
10
0
Order By: Relevance
“…To illustrate enantioselective drug-protein binding, classical methods, such as equilibrium dialysis (ED), ultrafiltration (UF) and ultracentrifugation (UC), are commonly combined with chiral separation techniques 27,28,29 . ED is an apparatus with two compartments separated by a semipermeable membrane, and only unbound drug molecules can permeate through the membrane.…”
Section: Methods and Modelsmentioning
confidence: 99%
See 1 more Smart Citation
“…To illustrate enantioselective drug-protein binding, classical methods, such as equilibrium dialysis (ED), ultrafiltration (UF) and ultracentrifugation (UC), are commonly combined with chiral separation techniques 27,28,29 . ED is an apparatus with two compartments separated by a semipermeable membrane, and only unbound drug molecules can permeate through the membrane.…”
Section: Methods and Modelsmentioning
confidence: 99%
“…Additionally, detailed information on the identity of the ligand binding pocket(s) and specific amino acid(s) of HSA that are responsible for this allosteric effect is needed. Lammers et al 90 showed the stereoselective binding of flurbiprofen (FBP) enantiomers and their methyl esters to HSA using time-resolved phosphorescence. Based on the phosphorescence lifetimes, R -flurbiprofen quenched Trp more effectively than S -flurbiprofen, in contrast to its methyl esters.…”
Section: Stereoselectivity Of Plasma Protein Binding To Chiral Drugsmentioning
confidence: 99%
“…3). Nevertheless, clinically (R,S)-flurbiprofen is used as a racemic mixture, not as an individual enantiomer [10][11][12]. (S)-enantiomer exhibits an inhibitory effect on cyclooxygenase (COX-2), thus anti-inflammatory action is determined.…”
Section: Another One Of the Broadly Applicable Nonsteroidal Anti-inflmentioning
confidence: 99%
“…Rather, it is a novel site located between subdomains IIA and IIB. This finding explains why there is only a partial quenching of HSA phosphorescence in the presence of FBP, 47 as FBP in that secondary site is not in direct contact with Trp214 as would be in site I, but at a distance ~10 Å. 50 In addition to the FBP/HSA complex, we also examine covalently linked dyads formed by (S)-and (R)-enantiomers of FBP and (S)-tryptophan methyl ester (TrpMe), in which the enantioselectivity is reversed.…”
Section: Introductionmentioning
confidence: 86%
“…In addition, flurbiprofen exhibits stereoselectivity in its pharmacokinetics, 45 and stereoselective binding to HSA has been shown to occur. 46,47 It is known that flurbiprofen binds preferentially to site II (benzodiazepine binding site) of HSA but also binds with remarkable affinity to another site. 46,48,49 Often this secondary binding site has been identified with well-known site I (warfarin binding site) of HSA.…”
Section: Introductionmentioning
confidence: 99%